PEMBINAAN USAHA MIKRO KECIL MENENGAH (UMKM) GIRI BALI BAMBOO MELALUI PENINGKATAN PRODUKSI - Luh Kadek Budi Martini; Mutria Farhaeni; Ni Putu Widiastuti; Putu Ade Wijana; Anak Agung Istri Ngurah Dyah Prami (Synergy and Society Service, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in national economic development. MSMEs have several advantages, including being able to overcome unemployment, namely being able to absorb labor, create new job opportunities, open new jobs, and also as a business solution for small communities. One of them is the Bali Giri Bamboo MSME which makes cutlery products using raw materials from bamboo, such as spoons, forks, glasses, tumblers, straws, bread knives, boxes for cosmetics and tissue holders. The solutions provided are (1) Procurement of machines/tools to increase the quantity and quality of production; (2) Training and assistance in using tools and making new products. The method used is providing technology in the form of tools and machines as well as providing training and assistance in using tools and making new products. The results of coaching for Bali Giri Bamboo MSMEs through the provision of tools in the form of lathe machines, drilling machines, complete packages of lathe holders, aluminum miter saws, magnetic drills, sitting planer machines, wood cutting table machines, wood profile machines, grinding machines, polishing grinding machines , round sanding machine, chuck set. Meanwhile, training and assistance makes, among other things: teapots, glasses, cosmetic containers, straws, bamboo speakers. By providing tools and training, it is hoped that Bali Giri Bamboo can improve product quality and quantity.